Ultra-Broadband Organic THz Generators: Influence of Substituents on THz Phonon Vibrations in Phenolic Parallel-Type Cation–Anion Assembly - Lee, Chae Won; Puc, Uros; Kim, Jongtaek; Jazbinsek, Mojca; Kwon, O. Pil (Advanced Optical Materials, 2024)
Organic terahertz (THz) crystals consist of polar molecules with various functional substituents, resulting in numerous molecular phonon vibrations in the THz frequency range. However, the effect of incorporating substituents into organic THz crystals on the resulting THz absorption is rather an unexplored area. In this work, by choosing an appropriate model system consisting of two benchmark organic nonlinear optical crystals, exhibiting an identical type of phenolic cation–anion assembly but different substituents, their ultra-broadband THz wave generation characteristics are demonstrated and investigated. Compared to the unsubstituted crystals, the substituted crystals possess one more methoxy substituent on highly polar cationic chromophores. Their vibrational modes and THz absorption characteristics are investigated theoretically by periodic density functional theory and experimentally by ultra-broadband THz spectroscopy up to 12 THz. In phenolic parallel-type cation–anion assembled organic THz crystals, the existence of a methoxy substituent differently influences the molecular vibrations in low and high THz frequency ranges. In the lower THz frequency range, the unsubstituted crystals exhibit additional strong entire molecular vibrations, the so-called cation-on-cation slipping vibrations, which do not exist in the substituted crystals. In contrast, the methoxy substituent leads to additional strong intramolecular vibrations in the higher THz frequency range.
Keywords: Cation-anions; Methoxy; Organic crystal; Organics; Phenolics; Phonon vibrations; Tera Hertz; Terahertz frequency range; Terahertz photonics; Ultra-broadband; organic crystals; phonons; THz photonics